Análise comparativa entre os métodos de determinação da taxa metabólica visando o equilíbrio entre o homem e o ambiente - Broday, Evandro Eduardo (2013)
Metabolic rate consists of the production of heat by the body and its incorrect determination can be linked to discrepancies between the model of the PMV and real thermal sensation collected in field studies. PMV (Predicted Mean Vote) is an index that predicts the mean value of the votes of a large group of people. Aiming at improve adherence to the PMV model and the real thermal sensation, this work established new values for the metabolic rate in two ways: one way being called "calculated" using the Newton’s Method and the other called "real" using a metabolic analyzer. Welder’s activities were evaluated, through the measurements of environmental and personal variables, during the full development of the activities determining new values of metabolic rate for this activity. It was determined, for this activity, new values of metabolic rate.The values found for calculated and real were, respectively, 178.63 and 145.46 W/m², different from the range provided by ISO 8996 (2004) for this activity (75 to 125 W/m²). It was verified which of the metabolic rate’s values was closer to the real thermal sensation of PMV. For this, it was made a linear regression between the PMV and the real thermal sensation in three ways: S x PMVtabulated (R² = 0.1749), S x PMVcalculated (R ² = 0.7481) and S x PMVreal (R ² = 0, 7854). It was found that the values obtained in "real" gave a higher coefficient of determination, and then being this the choice for the correction of the table. The table provides a Mpredicted and for the activities of the welder in a metal-mechanics industry, tabulated values can be multiplied by the correction coefficient 1.4648 in order to minimize inaccuracies. The PMVpredicted, obtained through the Mpredicted, when related to the actual thermal sensation, provides a coefficient of determination of 0.7511, thereby improving the model of the PMV.